FAKTOR YANG MEMPENGARUHI CASH HOLDING PERUSAHAAN MANUFAKTUR DI INDONESIA TAHUN 2016 – 2018 - Shinta Theresia, Sufiyati (Jurnal Paradigma Akuntansi, 2020)
The purpose of this study is to determine the effect of firm size, profitability, leverage, sales growth, and net working capital on cash holding in manufacture companies that is listed in Indonesia Stock Exchange (IDX) for the period of 2016 – 2018. The samples used in this research are 70 companies using purposive sampling method. According to chow test and hausman test used in Eviews 9.0 software, this model used fixed effect model. The result of this research is that profitability, leverage, and net working capital had positive and significant effect on cash holding, while firm size and sales growth had no effect on cash holding.